2011
DOI: 10.1002/jsfa.4731
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activities and antioxidant properties of polysaccharides from Monascus-fermented products in vitro

Abstract: These findings demonstrate that RMRP and RMDP have antioxidant and immunomodulation potential to be developed as novel dietary supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Moreover, antioxidative activity measured using DPPH radicals revealed the same relationships as the ABTS (2,2 0 azinobis-(3-ethylbenzthiazoline-6-sulfonic acid)) radical cation (ABTS* þ ) method, but the TEAC values were higher, because ABTS* þ can be dissolved in aqueous and organic media in which the antioxidative activity can be easily enhanced (42). Nonetheless, Tseng et al (4) reported that the scavenging effects of the Monascus-fermented products, RMRP, RMDP, and DP, on DPPH radicals were only 25.23%, 49.72%, and 21.03%, respectively. Thus, BECMHFs in this study were more beneficial for antioxidative activity.…”
Section: Safety and Sensitive Effects Of Skin Moisturizersmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, antioxidative activity measured using DPPH radicals revealed the same relationships as the ABTS (2,2 0 azinobis-(3-ethylbenzthiazoline-6-sulfonic acid)) radical cation (ABTS* þ ) method, but the TEAC values were higher, because ABTS* þ can be dissolved in aqueous and organic media in which the antioxidative activity can be easily enhanced (42). Nonetheless, Tseng et al (4) reported that the scavenging effects of the Monascus-fermented products, RMRP, RMDP, and DP, on DPPH radicals were only 25.23%, 49.72%, and 21.03%, respectively. Thus, BECMHFs in this study were more beneficial for antioxidative activity.…”
Section: Safety and Sensitive Effects Of Skin Moisturizersmentioning
confidence: 89%
“…Reactive oxygen species assay ROS were measured using the NBT reduction method (4,29), which can be used to determine the amount of intracellular O 2 À produced by phagocytic cells. The absorbance at 570 nm was detected using an ELx 800 universal microplate reader (BioTek Instruments, Inc., CA, USA).…”
Section: Superoxide Dismutase-like Activity Assaymentioning
confidence: 99%
“…a change in the structure of carbohydrate components during fermentation by Monascus (Lee, Hsu, Liao, & Pan, 2012). It has been demonstrated that the polysaccharide components in Monascus-fermented products might be responsible for the effective antioxidant properties (Tseng et al, 2012).…”
Section: Unfermented Heat-denatured Soybean Mealmentioning
confidence: 99%
“…The effects of CPP on RAW 264.7 cell proliferation were assessed using an MTT assay [13]. RAW 264.7 cells in DMEM medium containing 10% FBS were plated in a 96-well microplate (1 × 10 5 cells/well, in a volume of 100 l) for 24 h and then cultured with different concentrations of CPP and HPP (100-1500 g/ml) or LPS (50 g/ml) for 24 h. After incubation, MTT was added to each well to a final concentration of 0.5 mg/ml.…”
Section: Effects Of Cpp and Hpp On Raw 2647 Cell Proliferation In Vitromentioning
confidence: 99%